TO STUDY THE CLINICAL SPECTRUM OF ALCOHOL LIVER DISEASE IN TERTIARY CARE CENTER - Dr. Sagar Malviya; Dr. Dolly Joseph (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Alcoholic liver disease (ALD) is a major contributor to global morbidity and mortality, encompassing a spectrum of conditions from steatosis to cirrhosis.  AIM: To evaluate the demographic profile, alcohol intake patterns, and clinical spectrum of ALD in patients at a tertiary care hospital in India.Material and Methods: A single-center, hospital-based cross-sectional study was conducted over 18 months, including 100 adult patients with confirmed ALD. Data on demographics, alcohol consumption patterns, and clinical features were collected through structured interviews and clinical assessments. Laboratory parameters and ultrasound findings were also analyzed.Results:  Participants were predominantly male (92%), with a mean age of 48 years. The prevalence of alcoholic cirrhosis was 70% (including 28 patients with decompensated cirrhosis) and 30% had hepatic steatosis (fatty liver) and alcoholic hepatitis. Heavy alcohol consumption (≥720 units/month) was strongly associated with advanced ALD, including cirrhosis (86%) and decompensated cirrhosis (38%) (p < 0.001). Chronic alcohol consumption (>20 years) correlated with higher prevalence of cirrhosis (89%). Common clinical manifestations included jaundice (55%), ascites (35%), and hepatic encephalopathy (15%). Laboratory findings revealed elevated SGOT/SGPT ratios (>2), hypoalbuminemia, and anemia. Ultrasound abnormalities such as coarse liver echotexture were prevalent in 70%.Conclusion: This study highlights the role of heavy and prolonged alcohol consumption in disease progression. The findings underscore the need for targeted interventions to reduce alcohol-related liver damage and improve clinical outcomes.